A4.2 IL4–10 synerkine for the treatment of osteoarthritis. (13th February 2015) - Steen-Louws, C; Pustjens, MF; Mastbergen, SC; Hack, CE; van Roon, JAG; Lafeber, FPJG
Abstract : Background and objectives: Osteoarthritis (OA) is a degenerative joint disease, clinically characterised by joint pain and disability. Underlying structural changes are degeneration of articular cartilage, intra-articular inflammation with synovitis and changes in peri-articular and subchondral bone. The ideal drug to treat OA should have analgesic, anti-inflammatory and cartilage protective effects. To date, no such drug has been described. In human and animal in and ex-vivo models, the immunoregulatory cytokines interleukin 4 (IL-4) and interleukin 10 (IL-10), especially in combination therapy, can prevent joint degeneration effectively. To use the combined activities of both IL-4 and IL-10, we developed IL4–10 synerkine, preserving the functional activity of each cytokine. In several well-established animal models, we have shown the potential of IL4–10 synerkine to inhibit inflammatory pain in animal models. In this study, we evaluated the potential of the synerkine to reduce inflammation and to provide cartilage protection in an ex vivo model for human OA. Materials and methods: Osteoarthritic cartilage (n = 8) and synovium (n = 6) was obtained at joint replacement surgery and was cultured for 72 h in conditioned medium, in the presence or absence of equimolar concentrations of IL-4 (10 ng/ml), IL-10 (10 ng/ml), the combination of IL-4 and IL-10 (10 ng/ml + 10 ng/ml) and IL4-10 synerkine (20 ng/ml). After culture, cartilage was selected to study changes in proteoglycan (PG) synthesis and release. Supernatants of both cartilage and synovium cultures were collected for measurement of a broad spectrum of inflammatory mediators. Results: In both synovium and cartilage cultures, elevated levels of pro-inflammatory mediators like IL-6 (resp. 7.5 µg/mg and 531 µg/mg) and IL-8 (resp. 2.6 µg/mg and 142 µg/mg) were measured. These levels were strongly inhibited by the IL4-10 synerkine (about 80%; all p < 0.01). IL4-10 synerkine also showed a reducing effect on the release of other important mediators, like IL-1, MMP-1 and MMP-3, whereas levels of interleukin-1 receptor antagonist (IL-1RA) and tissue inhibitor of metalloproteinase-1 (TIMP-1) remained unchanged. Additionally, the synerkine had a beneficial effect on proteoglycan metabolism, inducing proteoglycan synthesis with 32%, while the proteoglycan release was slightly reduced (-1.3%). Conclusions: IL4-10 synerkine directly affects proteoglycan turnover and cytokine production of OA cartilage, combined with reduced secretion of inflammatory cytokines and proteases by OA synovial tissue. The immunoregulatory and cartilage protective effects in combination with it's analgesic effects, suggest that the synerkine is an effective disease modifying drug in the treatment of osteoarthritis.